(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The adverse effects of global warming and climate change, including increased emissions, ecological imbalance, heatwaves, droughts, and ozone depletion, have heightened the global emphasis on sustainability and environmental preservation. Green Human Resource Management has emerged as a key strategic tool in aligning employee objectives with sustainable business practices, enhancing corporate social responsibility, and strengthening organizational reputations. This study seeks to evaluate the current implementation of Green HRM practices within the IT industry in Central NCR of India and to analyze the factors influencing these practices concerning company size. A quantitative research approach was employed, utilizing a structured questionnaire distributed to IT employees. The questionnaire was divided into two sections: the first addressed demographic variables, and the second comprised 13 statements adapted from prior research to assess Green HRM adoption. Data from 422 respondents were analyzed using SPSS, with exploratory factor analysis (EFA) employed to identify key patterns. The results suggest that IT departments are more predisposed to adopting green practices, likely due to their operational characteristics and exposure to digital and sustainable technologies. The study’s limitations include unequal gender representation, demographic imbalances, and the absence of qualitative insights. It is recommended that developing countries prioritize the adoption of Green HRM practices, as elements such as green recruitment, selection, and reward systems contribute positively to organizational sustainability.